nLCA in bakery food products: state of the art and urgent needs - Cassarino, Martina; Giuberti, Gianluca; Morelli, Lorenzo; Trezzi, Marco; Pelattieri, Andrea; Manicardi, Loris; Scaglia, Pietro (Frontiers in Sustainable Food Systems, 2024)
This paper analyzes the nutri)onal life cycle assessment (LCA) of bakery products and the current state of the art. The analysis focuses on: 1) the importance of applying a methodology, such as LCA, in a general way, and the division into different stages considering the UNI EN ISO; 2) the development of nutri)onal LCA; 3) the difference between func)onal units in LCA and nutri)onal LCA; and 4) the different nutri)onal LCA approaches. The paper emphasizes the lack of nutri)onal LCA studies regarding the bakery category, underlining the urgent need for this type of inves)ga)on concerning this specific food sector.